Mechanisms of NOS1AP action on NMDA receptor-nNOS signaling - Courtney, Michael J.; Li, Li-Li; Lai, Yvonne Y. (Frontiers in Cellular Neuroscience, 2014)
NMDA receptors (NMDAR) are glutamate-gated calcium channels that play pivotal roles in fun-damental aspects of neuronal function. Dysregulated receptor function contributes to many disor-ders. Recruitment by NMDARs of calcium-dependent enzyme nNOS via PSD95 is seen as a key contributor to neuronal dysfunction. nNOS adaptor protein (NOS1AP), originally described as a competitor of PSD95:nNOS interaction, is regarded an inhibitor of NMDAR-driven nNOS function. In conditions of NMDAR hyperactivity such as excitotoxicity, one expects NOS1AP to be neuropro-tective. Conditions of NMDAR hypoactivity, as thought to occur in schizophrenia, might be exacer-bated by NOS1AP. Indeed GWAS have implicated NOS1AP and nNOS in schizophrenia. Several studies now indicate NOS1AP can mediate rather than inhibit NMDAR/nNOS-dependent responses, including excitotoxic signalling. Yet the concept of NOS1AP as an inhibitor of nNOS predominates in studies of human disease genetics. Here we review the experimental evidence to evaluate this apparent controversy, consider whether the known functions of NOS1AP might defend neurons against NMDAR dysregulation and highlight specific areas for future investigation to shed light on the functions of this adaptor protein.